THE EFFECT OF TAX AVOIDANCE, INSTITUTIONAL OWNERSHIP AND PROFITABILITY ON THE COST OF DEBT ON MANUFACTURING COMPANIES LISTED IN 2017-2019 ON THE INDONESIA STOCK EXCHANGE - Krisdayanti Parang; Juaniva Sidharta; Rutman Lumbantoruan (Universitas Kristen Indonesia, 2022)
The purpose of this study is to prove the effect of tax avoidance, institutional ownership, and profitability on cost of debt. The sample consisted of 71 manufactured firms in listed in Indonesian Stock Exchange from 2017‐2019 by using a purposive sampling method of 31 manufacturing. The dependent variable in this study is the Cost of Debt the independent variable is tax avoidance measured by the Current Effective Tax Rate (ETR) proxy, Institutional Ownership (KI) Profitability Return on Assets (ROA). The results showed that tax avoidance had a significant effect on the cost of debt, while institutional ownership and profitability had no significant effect on the cost of debt.Keywords: Tax Avoidance, Institutional ownership, Profitability, Cost of Debt.